2021
DOI: 10.1126/sciadv.abh1663
|View full text |Cite
|
Sign up to set email alerts
|

Atypical genomic cortical patterning in autism with poor early language outcome

Abstract: Cortical regionalization develops via genomic patterning along anterior-posterior (A-P) and dorsal-ventral (D-V) gradients. Here, we find that normative A-P and D-V genomic patterning of cortical surface area (SA) and thickness (CT), present in typically developing and autistic toddlers with good early language outcome, is absent in autistic toddlers with poor early language outcome. Autistic toddlers with poor early language outcome are instead specifically characterized by a secondary and independent genomic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

4
6

Authors

Journals

citations
Cited by 36 publications
(57 citation statements)
references
References 85 publications
5
52
0
Order By: Relevance
“…Furthermore, heritability analyses suggest a genetic basis to the organization of cortical surface area and thickness along principal anterior-posterior and dorsal-ventral aspects, respectively (Chen et al, 2012(Chen et al, , 2013Valk et al, 2020). Follow up work has suggested that these genetically imposed patterns are disrupted in developmental disorders (Ball et al, 2020;Lombardo et al, 2021). More recent complementary work has provided evidence for an isolated directional gradient of gene expression in the adult brain, relating this gradient to other brain (neurodegenerative) diseases (Vogel et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, heritability analyses suggest a genetic basis to the organization of cortical surface area and thickness along principal anterior-posterior and dorsal-ventral aspects, respectively (Chen et al, 2012(Chen et al, , 2013Valk et al, 2020). Follow up work has suggested that these genetically imposed patterns are disrupted in developmental disorders (Ball et al, 2020;Lombardo et al, 2021). More recent complementary work has provided evidence for an isolated directional gradient of gene expression in the adult brain, relating this gradient to other brain (neurodegenerative) diseases (Vogel et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…While the brain is largely an inaccessible tissue to assay mechanisms like gene expression in living patients, blood leukocyte gene expression has revealed a number of interesting brain-relevant characteristics that can be related to different phenotypes in living patients. Leukocyte expression patterns can be used in a classifier to predict diagnostic status [ 24 ], correlate with total brain size [ 25 ], and are related to large-scale functional neural systems response to speech [ 26 ], the patterning of thickness and surface area in the cerebral cortex [ 27 ], and social symptom severity [ 28 ]. Differentially expressed genes in blood leukocytes are part of extended gene networks that are linked to highly penetrant ASD-related mutations [ 28 ].…”
mentioning
confidence: 99%
“…In line with this, it has been shown that DHT increases proliferation of intermediate progenitors and basal radial glia (79). Also, differences in proliferative processes through symmetric cell division in IP and RG lead to atypical cortical expansion of surface area in autism (8082). These downstream consequence of DHT may impact excitatory neuronal signaling, due to expansion of surface area via increased number of cortical columns and neurons within each column.…”
Section: Discussionmentioning
confidence: 99%